Cryopreservation and Transplantation of Ovarian Tissue as Method of Endocrine and Reproductive Functions Restoration - Kiroshka, Viktoriya V. (Problems of Cryobiology and Cryomedicine, 2013)
The review represents the state of art in existing methods for cryopreservation and transplantation of ovarian tissue used for restoration of reproductive and endocrine function. The successful outcomes of their application are shown both in experimental animal models and in clinical practice. The paper describes the main technical obstacles, which should be overcome to introduce into clinic the methods of cryopreservation and transplantation of ovarian tissue.Probl Cryobiol Cryomed 2013; 23(1):4-14.